Matching Seeds to Needs - female farmers adapt to a changing climate in Ethiopia - Gotor, Elisabetta; Fadda, Carlo; Trincia, C. (Bioversity International, 2014)
Between 2010 and 2012 Bioversity International worked with partners and stakeholders in Ethiopia to develop an innovative low-cost strategy for managing risks to agricultural systems posed by the adverse effects of climate change. The objective, which the project indeed achieved, was to decrease vulnerability and enhance adaptive capacity in smallholder farming communities by increasing the intraspecific diversity of important food security crops using barley and durum wheat.